1975
DOI: 10.1073/pnas.72.2.586
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal collagen metabolism in cultured cells in osteogenesis imperfecta.

Abstract: Haziv, Israel, March 24-28, 1974. biosynthetic studies. To obtain maximal labeling of collagenous protein, the growth media were replaced with 10 ml of the Dulbecco-Vogt medium lacking glycine, lysine, glutamate, and serum but supplemented with ascorbic acid (50 ug/ml) and ,3-aminopropionitrile (50 Ag/ml) (10). Twenty microcuries each of [U-'4C]glycine, [U-14C]proline, and [U-14C]-lysine were added to each flask. Usually cells were exposed to label for 24 hr, except in the studies designed to measure the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1

Year Published

1975
1975
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(44 citation statements)
references
References 21 publications
3
40
1
Order By: Relevance
“…Sci. USA 72 (1975) We studied cultured collagenous material by a limited cleavage of medium and cell collagenous protein with pepsin to dissolve insoluble collagen and convert precursor forms to collagen (14). Type I and type III chains were separated by standard chromatographic methods (9)(10)(11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sci. USA 72 (1975) We studied cultured collagenous material by a limited cleavage of medium and cell collagenous protein with pepsin to dissolve insoluble collagen and convert precursor forms to collagen (14). Type I and type III chains were separated by standard chromatographic methods (9)(10)(11).…”
Section: Resultsmentioning
confidence: 99%
“…Skin biopsies were obtained from the left forearm of all other patients with a 4 mm punch. The (12)(13)(14).…”
Section: Methodsmentioning
confidence: 99%
“…In reexamining cultured cells derived from a well-studied patient (6,14,15,17,20) with lethal perinatal 01, we have found that the type I procollagen synthesized by these cells is not secreted at a normal rate, and we suggest that failure of secretion is secondary to a structural mutation in one or both proal(I) chains.…”
mentioning
confidence: 96%
“…Affected infants have major abnormalities in bone formation and extremely friable connective tissue (15). The distribution of clinical findings corresponds to the distribution of type I collagen in tissues (16), and decreased production of type I collagen has been observed in cells from a patient with lethal perinatal 01 (6,17).…”
mentioning
confidence: 99%
“…In one of the best studied variants of this type, a deletion of -500 base pairs was produced by a sporatic mutation of one allele for the proal(I) chain (17)(18)(19)(20)(21). The deletion excised three exons with 252 base pairs of coding sequences (21).…”
Section: Genes For Procollagensmentioning
confidence: 99%